Functional anatomy of the hand - Ione Sellars (South African Journal of Physiotherapy)
Aspects of the functional anatomy of the hand are described with special emphasis on the individual joints, especially the carpometacarpal joint of the thumb. Muscles responsible for joint movements are tabulated and movements of the hand as a whole are briefly discussed.